2010
DOI: 10.1002/cphc.201000105
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Effects in Atom Distribution and Electrochemical Properties of AuxPt1−x/Pt(111) Surface Alloys

Abstract: We report on the structural and electrochemical properties of Au(x)Pt(1-x) surface alloys prepared by Au vapour deposition onto Pt(111) followed by annealing to 1000 K. Driven by configurational entropy, Pt and Au atoms are distributed homogeneously over the surface. On the nm scale, however, atomically resolved scanning tunnelling microscopy images with chemical contrast reveal the formation of nm-sized Pt-rich and Au-rich aggregates, similar to the behaviour recently reported for Pd(x)Ru(1-x)/Ru(0001) [H. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 71 publications
11
47
0
Order By: Relevance
“…6d), the extension of the topmost Pt(100) lattice might also contribute to the ORR activity enhancement. Similar ECSA-dependent ORR activity enhancements are reported for annealed Au/Pt(111) by Bergbriter et al 29 and MBE-prepared Pt/Au(111) reported by us. 30 Therefore, ORR appears to require extended Pt lattices at the topmost surfaces of Pt/Au(hkl).…”
Section: Electrochemical Oxidation and Reduction Of The Mbe-preparedsupporting
confidence: 91%
“…6d), the extension of the topmost Pt(100) lattice might also contribute to the ORR activity enhancement. Similar ECSA-dependent ORR activity enhancements are reported for annealed Au/Pt(111) by Bergbriter et al 29 and MBE-prepared Pt/Au(111) reported by us. 30 Therefore, ORR appears to require extended Pt lattices at the topmost surfaces of Pt/Au(hkl).…”
Section: Electrochemical Oxidation and Reduction Of The Mbe-preparedsupporting
confidence: 91%
“…The extent of ensemble effect on Au/Pt(111) has been the subject of study of various publications 27,[44][45] . In these reports it is demonstrated that the process a surface atomic exchange may induce a modification on the surface atomic distribution that will have a direct impact on the reactivity of the surface as a whole.…”
Section: Resultsmentioning
confidence: 99%
“…the 0.3-nm-thick Pt layer almost covers the Au(1 1 1) substrate surface. Hoster et al [39] reported the electrochemical properties of Pt-Au alloys prepared through Au depositions on clean Pt(1 1 1) and subsequent thermal annealing in UHV. They showed that Q OHad decreased steeply with decreasing Pt ratio and deduced that the geometric influence of surface Au atoms is significant for OH ad/desorption behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, well-defined Pt-Au bimetallic alloys fabricated in UHV should shed some light on the understanding of electrode catalysis of the surfaces. Bergbriter et al fabricated Pt-Au surface alloys through Au deposition on a Pt(1 1 1) substrate and subsequent annealing in UHV conditions and elucidated the surface geometric effects on the electrochemical properties of the surface Pt atoms [39]. On the basis of scanning tunnelling microscopy (STM) and cyclic voltammetry (CV) measurements, they showed that electrochemical properties of Pt-Au bimetallic alloys are dominated by the surface atomic ratios of Pt; the charges for hydrogen and hydroxyl-related adsorptions (Q Had and Q OHad ) decrease with decreasing Pt content, although Q OHad is more sensitive than Q Had .…”
Section: Introductionmentioning
confidence: 99%